Molecular structure influence on bending behavior of polyester filaments examined using a modified cantilever bending test - Höhnemann, Tim; Himmler, Marcus; Schubert, Dirk W. (Journal of Applied Polymer Science, 2019)
An experimental setup used to measure the bending stiffness of polymer filaments based on existing cantilever approaches is presented. Additionally, it is utilized to evaluate the influence of molar mass and long‐chain branching on filaments of poly(butylene terephthalate), modified with a multifunctional chain extender. Using shear rheological analysis process limits for extrusion of the modified material were revealed, indicated by a change of the curve shape of van Gurp–Palmen plots. For the processable modified materials, it was found that increasing molar mass and degree of long‐chain branching, caused by the modification, raise the bending stiffness of filaments. Also the Young's modulus was found to increase with the amount of chain extender used, while no difference could be generated by using different linear molar grades of the polymer
Keywords: bending; crosslinking; fibers; mechanical properties; polyesters; polymer bristles; properties and characterization; rheology; spectroscopy; structure‐property relations